Analisis Risiko Potensi Bahaya dan Pengendaliannya Dengan Metode HIRADC pada PT. IGASAR Kota Padang Sumatera Barat - Taufiq Ihsan; Aulia Safitri; Dhywa Putra Dharossa (Jurnal Serambi Engineering, 2020)
PT IGASAR was one of the companies affiliated with PT Semen Padang with business activities in the fields of engineering, cement distribution, transportation, heavy equipment rental, cement-based building materials industry, manufacturing, general contractor, and developer. Some work accidents were still found in activities at this company. It was essential to making hazard identification, risk assessment, and determined the type of control in some areas. There are work accidents in PT IGASAR in as many as five cases in 2017 - 2018. One way was to use the Hazard Identification Risk Assessment Determine Control (HIRADC) Method. A risk analysis was done by looking at the opportunities and the severity of the hazards. Based on the results of the risk analysis, it was found that activities that were low risk, very high risk was absent while the medium risk was 100%. The risk control measures include the provision of personal protective equipment, the rule of safety signs, equipment maintenance, and the creation of road area boundaries.